2017
DOI: 10.1103/physreve.95.022105
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field-crystal model for ordered crystals

Abstract: We describe a general method to model multicomponent ordered crystals using the phase-field-crystal (PFC) formalism. As a test case, a generic B2 compound is investigated. We are able to produce a line of either first-order or second-order order-disorder phase transitions, features that have not been incorporated in existing PFC approaches. Further, it is found that the only elastic constant for B2 that depends on ordering is C_{11}. This B2 model is then used to study antiphase boundaries (APBs). The APBs are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Just dropping the ∇ · [n∇Ln] term, as done by Huang et al [24], means that the dynamics is not equivalent to a DDFT with mobility proportional to ρ. On the other hand, the alternative is to expand the logarithm up to O(n 4 ) in (51) in order to provide a nonlinear stabilizing term ( 1 12 n 4 ) in the free energy (57). However, in the original formulation, the logarithm comes from the ideal gas term in (10), and leads to a linear diffusive term in the dynamics.…”
Section: H Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Just dropping the ∇ · [n∇Ln] term, as done by Huang et al [24], means that the dynamics is not equivalent to a DDFT with mobility proportional to ρ. On the other hand, the alternative is to expand the logarithm up to O(n 4 ) in (51) in order to provide a nonlinear stabilizing term ( 1 12 n 4 ) in the free energy (57). However, in the original formulation, the logarithm comes from the ideal gas term in (10), and leads to a linear diffusive term in the dynamics.…”
Section: H Summarymentioning
confidence: 99%
“…Throughout we have made the simplest choices in the approximations, but other authors have made many other choices. For example, the original PFC paper [1], as well as later papers [22,24,[50][51][52], included a twocomponent (binary) version of the PFC model. Recently, Wang et al [53] took a much closer look at c (3) and c (4) , expressing these in terms of isotropic tensors and so allowing these functions to introduce bond angle dependence into the free energy.…”
Section: H Summarymentioning
confidence: 99%
“…al. [41] who effectively define σ 2 ∼ T /T o . This is choice is more consistent with the temperature dependence of the Debye-Waller factor observed in experiments.…”
Section: A a New Density Functional Approach: Expanding Around The Vmentioning
confidence: 99%
“…It has be shown that the method is derivable from the fundamental classical density functional theory (CDFT) [30,31], with certain approximations based on the Ramakrishnan and Yussouff [32] free energy formalism. Since its inception, the method has evolved to model structural phase transformations [33][34][35][36], alloy systems [30,37,38], multiferroic composite materials [39], order-disorder systems [40], nucleation and polymorphism [41,42], amorphous or glass transitions [43,44], quasicrystals [45] and crystal plasticity [46]. Through coarse graining procedures, the methodology may be used to generate models that operate on mesoscopic length scales.…”
Section: Introductionmentioning
confidence: 99%